Winners and losers: analysing post‐disaster spatial economic demand shift. Issue 4 (6th September 2013) - Xiao, Yu; Nilawar, Uttara
Abstract : Disasters produce winners and losers. This paper evaluates such winners and losers in a spatial context. The hypothesis is that, because of severe damage to the core disaster area and the constraints associated with the cost of transportation, economic demand would shift to the immediate edge of the disaster zone where either minor or no damage is observed. Empirical analysis of growth patterns in counties/parishes in the states of Alabama, Louisiana, and Mississippi in the United States after Hurricane Katrina (August 2005) verified the spatial demand shift hypothesis. The study found that the post‐Katrina core disaster area became a 'doughnut hole' of low income and employment growth, surrounded by a ring of high growth counties/parishes on the edge of the hole. The short‐run adjustment in growth rates may have altered permanently the spatial distribution of employment and income both at the core and in the areas at the edge.